1998
DOI: 10.1086/515021
|View full text |Cite
|
Sign up to set email alerts
|

Are the Duke Criteria Superior to the Beth Israel Criteria for the Diagnosis of Infective Endocarditis in Children?

Abstract: Accurate diagnosis of infective endocarditis may be difficult. The Beth Israel criteria and the newer Duke criteria assign probability to the diagnosis of infective endocarditis on the basis of the presence of common features and manifestations. We reviewed 111 cases of pediatric infective endocarditis diagnosed and treated over 19 years. Each case was classified by the two criteria, and the results were compared. Of 111 cases, 73 (66%) and 18 (16%) were classified as definite by the Duke criteria and the Beth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(51 citation statements)
references
References 13 publications
(3 reference statements)
3
42
0
4
Order By: Relevance
“…The similar frequency in male and female patients in our analyses stands in contrast to the male predominance in infections in general and IE specifically. [12][13][14] We found that S aureus was the most common causative organism and that prosthetic valve IE was caused by organisms similar to those affecting patients without prosthetic valves; these data are consistent with other recent reports on IE. 1,2,14 The mortality rate in the KID, 5.3%, was lower than that reported in the adult population (18% to 23%) 15,16 or in recent pediatric IE series from large clinical centers caring for children with the most complex forms of CHD (10% to 11%).…”
Section: Discussionsupporting
confidence: 91%
“…The similar frequency in male and female patients in our analyses stands in contrast to the male predominance in infections in general and IE specifically. [12][13][14] We found that S aureus was the most common causative organism and that prosthetic valve IE was caused by organisms similar to those affecting patients without prosthetic valves; these data are consistent with other recent reports on IE. 1,2,14 The mortality rate in the KID, 5.3%, was lower than that reported in the adult population (18% to 23%) 15,16 or in recent pediatric IE series from large clinical centers caring for children with the most complex forms of CHD (10% to 11%).…”
Section: Discussionsupporting
confidence: 91%
“…Ferrieri et al conducted a review of the literature and found that VGS was the most common cause of IE in children. The studies reviewed found VGS to be the cause of between 32 and 43% of cases (15,30,36,51). In addition, 27 to 33% of IE was caused by S. aureus, which was the second most common etiologic agent.…”
Section: Clinical Significancementioning
confidence: 99%
“…Clinically definite IE by the Duke criteria requires the presence of 2 major criteria, 1 major criterion and 3 minor criteria, or 5 minor criteria (Table 1). Direct comparison of the Duke and Beth Israel criteria has been made in 11 major studies 5,[7][8][9][10][11][12][13][14][15][16] including nearly 1700 patients comprising geographically and clinically diverse groups (adult, pediatric, elderly [aged Ͼ60 years], patients from the community, those with and without IVDA, and patients with both native and prosthetic valves). These studies 5,[7][8][9][10][11][12][13][14][15][16] have confirmed the improved sensitivity of the Duke criteria and the diagnostic utility of echocardiography in identifying clinically definite cases (Table 3).…”
Section: Diagnosis Clinical Criteriamentioning
confidence: 99%